2012
DOI: 10.1111/j.1745-4549.2012.00771.x
|View full text |Cite
|
Sign up to set email alerts
|

Basil (Ocimum Basilicum L.) as a Natural Antioxidant

Abstract: The antioxidant activity from basil ethanol extract, the effect on oxidative stability, total polar compounds, tocopherols levels and fatty acid profile in soybean oil under thermoxidation were evaluated. The basil leaves were dried in lyophilizer, ground and subjected to extraction with ethanol. The soybean oil (SO), soybean oil with 50 mg/kg of tert‐butylhydroquinone (TBHQ), soybean oil with 3,000 mg/kg of extract (BE) and soybean oil with 3,000 mg/kg of extract and 50 mg/kg of TBHQ (mixture) treatments were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 20 publications
2
11
0
1
Order By: Relevance
“…These values were in agreement with Veronezi et al ( 2014 ) studies. However, Chowdhury et al ( 2007 ) studies showed that the total content of MUFA and PUFA in SBO was similar to our results, but the percentage of monounsaturated and polyunsaturated fatty acids in sunflower oil were different.…”
Section: Resultssupporting
confidence: 93%
“…These values were in agreement with Veronezi et al ( 2014 ) studies. However, Chowdhury et al ( 2007 ) studies showed that the total content of MUFA and PUFA in SBO was similar to our results, but the percentage of monounsaturated and polyunsaturated fatty acids in sunflower oil were different.…”
Section: Resultssupporting
confidence: 93%
“…Veronezi et al . () found that in the treatment with soybean oil with 3,000 mg/kg of basil extract, the oxidative stability remained stable up to 10 h of heating at a temperature of 180 ± 5C, whereas in the mixture treatment (soybean oil with the addition of a mixture of 3,000 mg/kg of basil extract and 50 mg/kg TBHQ), it remained stable for a period of 20 h. Angelo and Jorge () observed that the antioxidant capacity of coriander and ascorbyl palmitate extract (added in combination) increased the induction period of sunflower oil when compared with the application of each antioxidant isolatedly. In the same way, in a study performed by Luzia and Jorge (), the addition of lemon seed extract (2,400 mg/kg) in combination with TBHQ (25 mg/kg) in soybean oil presented greater efficiency in the protection of oil than when TBHQ was used isolatedly and in higher concentrations (50 mg/kg).…”
Section: Resultsmentioning
confidence: 99%
“…However, no significant difference (P>0.05) was observed among fresh samples exposed to three different types of solvent. Veronezi et al (2014) reported 31% of antioxidant activity of basil by using DPPH assay. Additionally, 73.75% of DPPH inhibition in Thai basil was reported by Naidu et al (2016).…”
Section: Antioxidant Activity Assays (Dpph and Frap)mentioning
confidence: 99%